Liberia : Second Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of Performance Criteria and Modification of a Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Liberia's Second Review Under the Extended Credit Facility (ECF) Arrangement and Request for Waiver of Nonobservance of Performance Criteria and Modification of a Performance Criterion. Program performance has weakened relative to the previous review, as well as the former ECF-supported arrangement. Three out of six performance criteria and two out of four indicative targets were missed. The IMF staff supports the completion of the second review of the ECF arrangement and the authorities' request for waivers of performance criteria and modification of the domestic financing performance criterion.